Elevated Vascular Level of ortho-Tyrosine Contributes to the Impairment of Insulin-Induced Arterial Relaxation - Szijártó, I. A.; Molnár, G. A.; Mikolás, E.; Fisi, V.; Cseh, J.; Laczy, B.; Kovács, T.; Böddi, K.; Takátsy, A.; Gollasch, M.; Koller, A.; Wittmann, I. (Hormone and Metabolic Research, 2014)
Previous studies have shown that in diabetes mellitus, insulin-induced relaxation of arteries is impaired and the level of ortho-tyrosine (o-Tyr), an oxidized amino acid is increased. Thus, we hypothesized that elevated vascular level of o-Tyr contributes to the impairment of insulin-induced vascular relaxation. Rats were fed with o-Tyr for 4 weeks. Insulin-induced vasomotor responses of isolated femoral artery were studied using wire myography. Vascular o-Tyr content was measured by HPLC, whereas immunoblot analyses were preformed to detect eNOS phosphorylation. Sustained oral supplementation of rats with o-Tyr increased the content of o-Tyr in the arterial wall and significantly reduced the relaxations to insulin. Sustained supplementation of cultured endothelial cells with o-Tyr increased the incorporation of o-Tyr and mitigated eNOS Ser (1 177) phosphorylation to insulin. Increasing arterial wall o-Tyr level attenuates insulin-induced relaxation – at least in part – by decreasing eNOS activation. Elevated level of o-Tyr could be an underlying mechanism for vasomotor dysfunction in diabetes mellitus.
Keywords: insulin; vasomotor function; ortho-tyrosine; eNOS